2008
DOI: 10.5194/acp-8-2189-2008
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Intercomparison of formaldehyde measurements at the atmosphere simulation chamber SAPHIR

Abstract: Abstract. The atmosphere simulation chamber SAPHIR at the Research Centre Jülich was used to test the suitability of state-of-the-art analytical instruments for the measurement of gas-phase formaldehyde (HCHO) in air. Five analyzers based on four different sensing principles were deployed: a differential optical absorption spectrometer (DOAS), cartridges for 2,4-dinitrophenylhydrazine (DNPH) derivatization followed by off-line high pressure liquid chromatography (HPLC) analysis, two different types of commerci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 34 publications
1
109
0
2
Order By: Relevance
“…Moreover, it is easy to measure RH and T of ambient air for further correction of HCHO data by PTR-MS in practice. Wisthaler et al (2008) reported the intercomparison between PTR-MS and DNPH-HPLC in an atmosphere simulation chamber; good agreement was found between PTR-MS and DNPH-HPLC while ambient air was introduced into the chamber, but the concentration of HCHO measured by DNPH-HPLC was less than that by PTR-MS, which could be caused by some interferences for the DNPH-HPLC method or the varying performance of the KI ozone scrubber. Overestimation of DNPH-HPLC for HCHO in the presence of NO 2 was also reported by Herrington and Hays (2012), because NO can be oxidized to NO 2 in the upstream ozone scrubber, and NO 2 will react with DNPH to form 2,4-dinitrophenyl azide (DNPA), which has similar chromatographic properties to the formaldehyde-DNP-hydrazone.…”
Section: Ptr-ms Vs Dnph-hplcmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it is easy to measure RH and T of ambient air for further correction of HCHO data by PTR-MS in practice. Wisthaler et al (2008) reported the intercomparison between PTR-MS and DNPH-HPLC in an atmosphere simulation chamber; good agreement was found between PTR-MS and DNPH-HPLC while ambient air was introduced into the chamber, but the concentration of HCHO measured by DNPH-HPLC was less than that by PTR-MS, which could be caused by some interferences for the DNPH-HPLC method or the varying performance of the KI ozone scrubber. Overestimation of DNPH-HPLC for HCHO in the presence of NO 2 was also reported by Herrington and Hays (2012), because NO can be oxidized to NO 2 in the upstream ozone scrubber, and NO 2 will react with DNPH to form 2,4-dinitrophenyl azide (DNPA), which has similar chromatographic properties to the formaldehyde-DNP-hydrazone.…”
Section: Ptr-ms Vs Dnph-hplcmentioning
confidence: 99%
“…Good agreement was found between PTR-MS and DOAS in both moun- tain areas (slope = 1.01) (Inomata et al, 2008) and urban areas (slope = 1.17) (Warneke et al, 2011b). HCHO measurement by DNPH-HPLC was compared to PTR-MS in an atmosphere simulation chamber by Wisthaler et al (2008), and significant lower HCHO levels by DNPH-HPLC were observed in dry synthetic air because of hydrazine-to-hydrazone conversion. Proton-transfer-reaction mass-spectrometry (PIT-MS), atmospheric pressure chemical ionization mass spectrometry (AP-CIMS), and GC- MS/FID were chosen as alternative monitoring methods for acetaldehyde, acetone, and MEK.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrument has been described and characterized in great detail over the last several years (Blake et al, 2009;de Gouw and Warneke, 2007;Hansel et al, 1995Hansel et al, , 1999Lindinger et al, 1998a, b;Warneke et al, 2001Warneke et al, , 2003Warneke et al, , 2011b and many successful intercomparisons with other techniques such as gas chromatography mass spectrometry (GC-MS) have demonstrated the sensitivity and the selectivity of PTR-QMS de Gouw and Warneke, 2007;Haase et al, 2012;Wisthaler et al, 2008). PTR-QMS is a chemical ionization mass spectrometry technique that detects VOCs using proton transfer reactions with H 3 O + , but has the drawback that only the nominal unitresolution mass of one VOC at a time can be determined.…”
Section: Introductionmentioning
confidence: 99%